Genetic Analysis of Cytokine Promoters in Nonhuman Primates: Implications for Th1/Th2 Profile Characteristics and SIV Disease Pathogenesis - Pavel Bostik; Melanie Watkins; Francois Villinger; Aftab A. Ansari (Clinical and Developmental Immunology)
The shift from a predominant synthesis of prototype Th1 cytokines to Th2 or Th0 type of cytokines by antigen activated PBMC's from HIV infected humans and SIV infected disease susceptible rhesus macaques (RM) has been shown to be associated with disease progression. Paradoxically, antigen activated PBMC's from sooty mangabeys (SM), which are naturally infected with SIV and are disease resistant despite high viral loads, maintain a predominant Th2 cytokine profile. It has been reasoned that the resistance to perturbations of cytokine synthesis by slow and/or nonprogressor HIV infected patients and SIV infected disease susceptible RM is secondary to inherited polymorphisms within the promoter regions for cytokines. Similar promoter polymorphisms could also contribute to the cytokine profile of PBMC's from SM. To address this issue promoter regions for the major Th1/Th2 cytokines from RM and SM were cloned and sequenced. Sequence analysis of promoter fragments of IL-4, IL-10, IL-12 p40, IFN-gamma and TNF-alpha from the two monkey species showed varying degree of homology ranging from high degree of homology detected for IFN-gamma promoter (>99%) to relatively high degree of polymorphism detected for TNF-alpha promoter (94% homology). In addition, several variable regions within the promoters of IL-12 p40, IL-10 and TNF-alpha in the two species contain polymorphisms in sequences that constitute binding sites of known transcription factors (TF). Such differences are likely to differentially bind TF and thus either qualitatively and/or quantitatively affect the regulation of cytokine synthesis in these two species and potentially contribute to disease progression and/or resistance.